A Review of Intellectually Property Right and Biodiversity (Journal of Advances and Scholarly Researches in Allied Education, 2025)
At the national and international levels, the connection between biodiversity and intellectual property rights (IPRs) is a hotly debated topic. The bulk of the world's biodiversity is found in poor countries, which desire equitable ownership and fair benefit-sharing from genetic resources, while wealthier nations support tighter monopolistic protections to spur innovation and ensure profits. The difficulties of striking a balance between the commercial exploitation of biological resources and biodiversity protection are highlighted by international accords like the TRIPS Agreement and the Convention on Biological Diversity (CBD). With special attention to India's flexible strategy as a signatory to several treaties, this analysis explores the changing legal and regulatory frameworks pertaining to patents, geographical indications, plant breeders' rights, farmers' rights, and sovereign rights. Review the pressing need for a new and more inclusive global governance structure by highlighting the increasing conflict between the demands for fair benefit distribution, economic exploitation, and conservation concerns.